2014
DOI: 10.1007/s11085-014-9501-8
|View full text |Cite
|
Sign up to set email alerts
|

The Onset of Potassium Chloride Induced High Temperature Corrosion: A Novel Experimental Approach

Abstract: The present study investigates the early stages of the oxide layer degradation process of Sanicro 28 (Fe31Cr27Ni) stainless steel when exposed to KCl at 450 and 535°C. A novel combinatory technique was developed and utilized, where CA was employed as a qualitative method to follow the varying stages of the onset of the corrosion reaction. XPS was then used to identify the elemental distribution and depth profile within the oxide layer at each identified reaction stage, and the resulting change in surface morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…As a result, corrosion products, such as Fe/Cr chlorides, oxides, chromates, etc. are formed [2,5,6,7,8,9]. Most of the corrosion products form a complex eutectic mixture with the components present in the deposit [10].…”
Section: Effect Of Deposit Type and Sintering Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, corrosion products, such as Fe/Cr chlorides, oxides, chromates, etc. are formed [2,5,6,7,8,9]. Most of the corrosion products form a complex eutectic mixture with the components present in the deposit [10].…”
Section: Effect Of Deposit Type and Sintering Temperaturementioning
confidence: 99%
“…Several corrosion studies in literature indicate that the rate of corrosion decreases considerably over time [2,5,12]. The change in melt fraction brought about by increasing corrosion is probably not significant enough to observe reliable changes in adhesion strength.…”
Section: Effect Of Sintering Timementioning
confidence: 99%
“…), a highly destructive fluxing of Cr2O3 scales. [35,38,40,41,43,48,73,87] Where the sulphate scale was thick and dense, it also prevented chromium vaporisation and instead, CrCl3/Cr2O3 scale was found beneath the sulphate scale.…”
Section: Corrosion Resistance Of Aisi 304: the Effect Of Chromium Alloy Ing In The Conditions Of The Heat Recovery Boilermentioning
confidence: 99%
“…The coupled effect of 40% H 2 O + 5% O 2 in the gas phase and small amounts of KCl deposit on stainless alloys at 600°C was investigated by [10,11] focusing on the mechanism of breakdown of the protective oxide by potassium to form potassium chromate. Sui et al 12 used chronoamperometry together with XPS (to distinguish Cr 3+ and Cr 6+ in the corrosion product) thus revealing that the formation of potassium chromate on UNS N08028 steel already occurred in the first 3 minutes of reaction at 450°C and 535°C. More recently, the use of O 18 to label different oxygen species in the gas phase (H 2 O and O 2 ) indicated that when KCl is present, oxygen from O 2 contributes primarily to the formation of chromate 13 .…”
Section: Introductionmentioning
confidence: 99%